2022
DOI: 10.54394/ycep9777
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact

Abstract: Environmental regulations provide protection for both environmental assets and the livelihoods of communities that depend on these assets. The analysis evaluates the Environmental Impact Assessment (EIA) processes for proponents of industrial projects in Bangladesh, Cambodia, Indonesia and Viet Nam. The paper finds that enhanced environmental outcomes can be achieved by greater awareness among proponents of the links between environmental management (as facilitated by the EIA process) and sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For major textile‐producing countries such as Bangladesh, this exacerbates existing water crises, including severe water pollution. These issues are particularly pronounced in delta‐based regions like Dhaka, where untreated effluents have rendered rivers biologically “dead” (Sharpe & Retamal, 2021). These environmental challenges are further compounded by industrial pollution—responsible for 60% of pollution in the Dhaka watershed—with garment factories contributing significantly to these stresses (NRDC, 2012; Sharpe & Retamal, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For major textile‐producing countries such as Bangladesh, this exacerbates existing water crises, including severe water pollution. These issues are particularly pronounced in delta‐based regions like Dhaka, where untreated effluents have rendered rivers biologically “dead” (Sharpe & Retamal, 2021). These environmental challenges are further compounded by industrial pollution—responsible for 60% of pollution in the Dhaka watershed—with garment factories contributing significantly to these stresses (NRDC, 2012; Sharpe & Retamal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These issues are particularly pronounced in delta‐based regions like Dhaka, where untreated effluents have rendered rivers biologically “dead” (Sharpe & Retamal, 2021). These environmental challenges are further compounded by industrial pollution—responsible for 60% of pollution in the Dhaka watershed—with garment factories contributing significantly to these stresses (NRDC, 2012; Sharpe & Retamal, 2021). Untreated or inadequately treated textile wastewater is regularly discharged into the environment, resulting in the contamination of groundwater and surface water sources, and contributing to water scarcity—all of which negatively impact both the climate and human health (Makene et al, 2019; Tarkwa et al, 2019; Yaseen & Scholz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EIA serves as a management tool to determine the impact of development projects and create mitigation strategies to address potential impacts in addition to supporting decision-making [1]. In 2021 International Labour Organization assessed the impact of the EIA in the textile and garment sector in Bangladesh, Cambodia, Indonesia, and Viet Nam, where they found that, according to Greenpeace, simply put the Indonesian monitoring system lacks openness, making information on discharge permits, monitoring data, and compliance difficult for the general public to access [2]. On the other hand, Indonesia's EIA regulations are considered quite comprehensive, and some progress has been made to improve public participation and transparency [3].…”
Section: Introductionmentioning
confidence: 99%
“…With its sprawling archipelago comprising over 17,000 islands, Indonesia is a nation where verdant rainforests teem with biodiversity, pristine beaches kiss the azure waters, and ancient cultural heritage intertwines with nature's grandeur (Sharpe, Retamal, & Martinez-Fernandez, 2022). However, beneath its natural splendor lies a pressing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…This study seeks to fill this gap by providing an in-depth analysis of the Indonesian EIA system, shedding light on its strengths, weaknesses, and areas for improvement. Additionally, Indonesia's dynamic social, economic, and political landscape presents a complex context for the implementation of EIA (Sharpe et al, 2022). Rapid industrialization, population growth, and urbanization have strained the delicate balance between development and environmental preservation.…”
Section: Introductionmentioning
confidence: 99%